RATIONAL PHARMACOTHERAPY IN TAKOTSUBO CARDIOMYOPATHY - S. Marchev; T. Vekov (Столичная издательская компания, 2015)
Rational pharmacotherapy in Takotsubo cardiomyopathy is based on clinical picture and data of functional and laboratory investigations of concrete patient. In patients with hypotension and moderate-to-severe left ventricle outflow tract obstruction inotropic agents must not to be used because they can worsen the degree of obstruction. In these patients beta blockers can improve hemodynamics by causing resolution of the obstruction. If intraventricular thrombus is detected, anticoagulation for at least 3 months is recommended. The duration of anticoagulant therapy may be modified depending on the extent of cardiac function recovery and thrombus resolution. For patients without thrombus but with severe left ventricular dysfunction, anticoagulation is recommended until the akinesis or dyskinesis has resolved but not more than 3 months.